Estudio anatómico de Hippocratea excelsa HBK. (Hippocrateaceae) - Villa Fernandez, Marcelina Graciela; Barajas-Morales, Josefina; Angeles, Guillermo (Instituto de Ecología, A.C., 1998)
An anatomical description for the leaf, secondary xylem and bark of stem and root of Hippocratea excelsa HBK. is presented. The bark of this species, popularly known as "cancerina" is traditionally used in the treatment of different diseases. Economically important compounds (e.g. guttapercha) are also obtained from the bark. The leaf has stomata of actinocytic type, its palisade parenchyma contains an abundance of intercellular spaces, and tannins and druses are found in the epidermic cells. Secondary xylem of stem and root presents diffuse porosity, solitary vessels, scanty paratracheal and diffuse-in aggregates apotracheal parenchyma, and multiseriate rays. Starch and other non identified compounds were observed in the secondary xylem parenchyma of the root. The root bark has abundant tannins, solitary crystals and fibers of two different forms: some with spindle-shaped and some others with blunt ends.